(untitled) (Fiep Bulletin - online, 2016)
Systemic Arterial Hypertension (SAH) is considered one of the major public health problems in Brazil, due to its high prevalence and low control. The aging process increases the risk of developing chronic diseases, with systemic arterial hypertension (SAH) considered a major disease in the field of Public Health Associated with the aging process, is hearing loss, whose prevalence in the elderly is about 63%. Studies suggest that changes in cochlear activity may be due to metabolic diseases, and hypertension a disease that can cause damage to the auditory system. Aimed to describe the demographic and socioeconomic profile of hearing impaired adults and elders attended in Family Health Strategies of Macaé, RJ. We conducted a descriptive, quantitative study of primary basis in the period between December 2013 and February 2014, with adults and elders attended in 7 Family Health Strategies of Macaé. Previously trained scholarship holders interviewed the selected group, using a structured questionnaire. A total of 338 adults and elderly with hypertension in FHT ’s were interviewed, representing about 36% of the assisted population, detecting 6 % of those with hearing disabilities with an average (±SD) age of 60.7±11 years, 16.7% male and 83.3% female. According to the color of skin, it was found that 38.9% reported being white, 33.4% black and 27.7% mixed. Regarding the origin, it was found that 83.3% were from the Southeast of Brazil. The average household income (AHI) of the surveyed users was 55.6% between 1 and 3 MW. It was observed a mean (± SD) of dependants of an average household income (AHI) of 2.7 ± 2.1 MW. The mean (± SD) time of diagnosis of SAH of the users was 11.7±7.5 years. The majority of respondents are elderly females from the Southeast of Brazil, with an average income of 1-3 MW.